Bulky cyclopentadienyl chromium complexes as ethene trimerisation catalyst precursors - Blom, Burgert (Department of Chemistry, 2016)
The process of ethene trimerisation to 1-hexene, has recently attracted considerable interest, in light of the usefulness of 1-hexene industrially. In this project the process of catalytic ethene trimerisation, using bulky cyclopentad ienyl chromium complexes was investigated. Firstly, a series of known and novel bulky cyclopentadiene ligands, of the type, C₅Ph₄RH (R = H, alkyl, aromatic or substituted aromatic group) were synthesised. Four routes were investigated. (i) Making use of an in situ generated bis-lithium intermediate, resulting in the formation of 1 ,2,3,4,5-pentaphenyl cyclopenta-1 ,3-diene and 1 ,2,3,4-tetraphenylcyclopenta-1 ,3-diene. (ii) The attempted use of a metallation I alkylation route which was unsuccessful. (iii) The use of tetracyclone as starting material, reacted with alkyl likthium reagents, or alkyl Grignard reagents which resulted in the formation of ligands, of the type C₅Ph₄R, with R in the 5 position of the ring (R = n-butyl, tertbutyl, hexyl). Unexpected side reactions afforded the isolation of two ligands of the type C₅Ph₄R, R = 1-propeneyl and ethyl, both with the terminal alkene function, saturated. (iv) The use of a Pd catalysed route, making use of Cp₂ZrCI₂ as source of cyclopentadiene, resulted in the successful isolation of the cyclopentadiene, C₅Ar₅H (Ar = C₆Me₂H₃). All new compounds were successfully characterised using NMR, IR, MS and elemental analysis. A stable Fe(II) model complex, bis-tetraphenylcyclopentadienyl iron, was prepared and cyclic voltametry conducted on it, to investigate the effect of phenyl substituents on a Cp ligand in the reduction I oxidation potential of the iron(II) centre. This study showed that phenyl rings on a cyclopentadiene ligand have a significant effect on the redox potential of Fe(II); this trend could possibly be expected with other metals, in particular chromium .